Uptake of Leucine, Chitin, and Iron by Prokaryotic Groups during Spring Phytoplankton Blooms Induced by Natural Iron Fertilization off Kerguelen Island (Southern Ocean) - Fourquez, Marion; Beier, Sara; Jongmans, Elanor; Hunter, Robert; Obernosterer, Ingrid (Frontiers in Marine Science, 2016)
Iron and carbon are essential for microbial heterotrophic activity, but the bioavailability of these elements is low in surface waters of the Southern Ocean. Whether the access to iron and carbon differs among phylogenetic groups of prokaryotes is barely known. To address this question we used iron (55FeCl3), and the carbon compounds chitin (3H-Diacetylchitobiose) and leucine (3H-leucine) as model substrates in combination with MICRO-CARD-FISH during spring phytoplankton blooms induced by natural iron fertilization off Kerguelen Island (KErguelen Ocean and Plateau compared Study 2 - KEOPS2; October-November 2011). The application of probes at broad phylogenetic levels indicated an overall similar community composition in surface waters at the 8 investigated sites. The relative contributions of the prokaryotic groups to abundance revealed a strong positive relationship with their respective contributions to the leucine-active community (p<0.0001; r=0.93). This relationship was much weaker for chitin (p<0.001; r=0.51) and absent for iron (p>0.05; r=0.26). These results suggest preferential uptake of iron and chitin by some prokaryotic groups. SAR11 and Cytophaga-Flavobacterium-Bacteroides (CFB) were the dominant contributors to the leucine-active community, while CFB and Archaea had the highest contributions to the chitin-active community. By contrast, Gammaproteobacteria, including SAR86, and CFB revealed the highest contributions to the iron-active community. We found several correlations between the group-specific fractions of active cells for a given substrate and most of them included CFB, pointing to the potential importance of microbial interactions for iron and carbon cycling in the Southern Ocean.